Power snatch execution asymmetry capturing method - Khasin, L. A.; Drozdov, A. L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and test benefits of a power snatch execution asymmetry capturing method applicable in the weightlifting elite training systems. Methods and structure of the study. We used in the study detailed power snatch video captures produced by three high-speed cameras shooting from different angles. Cameras 1 and 2 were fixed 7m from the shaft butt on the right and left sides (respectively) of the weightlifting platform with the shooting axes parallel to the bar shaft. Camera 3 was fixed 10m far from the shaft perpendicular to the shaft center for the full-face shooting. We sampled for the power snatch kinematics analysis an elite women`s weightlifting Master of Sport competing in the 59kg weight class. Results and conclusion. We analyzed an individual asymmetry of the power snatch execution by elite weightlifter L to compute the horizontal/ vertical tilts and detect the tilt/ imbalance startup moment - and find reasons for the power snatch asymmetry. We also found that the vertical tilt/ imbalance starts up and grows after the shaft-hips contact. Despite the contact points and movement times of the right and left plates being even, the horizontal acceleration peaks and forces on the both plates were found to differ. In the analyzed power snatch sequence, the right plate was found to move faster with higher acceleration than the left one to force a vertical tilt on the weight. Horizontal tilt of the weight was found to start in the depreciation (pre-dip-under) phase, with a positive acceleration peak on the left butt. As a result, the vertical speeds of the right and left plates were different to result in the weight control asymmetry. This power snatch execution tilt/ asymmetry is may be explained by the individual anthropometrics-specific speed-strength imbalances plus a compensatory grip asymmetry.